Inflammation of mammary adipose tissue occurs in overweight and obese patients exhibiting early-stage breast cancer - Charlotte Vaysse; Jon Lømo; Øystein Garred; Frøydis Fjeldheim; Trygve Lofteroed; Ellen Schlichting; Anne McTiernan; Hanne Frydenberg; Anders Husøy; Steinar Lundgren; Morten W. Fagerland; Elin Richardsen; et al. (npj Breast Cancer, 2017)
Immunology: Weight tied to inflammation in fat surrounding tumor Overweight and obese women with breast cancer show more inflammation in their mammary fat tissue, creating an environment favorable to tumor growth. In a study performed at the Oslo University Hospital, Norway, Charlotte Vaysse and colleagues characterized the fat cells found close to the breast tumors of 107 patients with early-stage disease. The researchers showed that overweight and obese women were more likely to have clusters of pro-inflammatory macrophage cells within the fat tissue close to the tumors than normal weight women. They further divided the patients according to whether they’d gone through menopause or not, and found that body mass index was a good predictor of fat cell inflammatory status in postmenopausal women, whereas belly fat percentage was a more accurate measure for premenopausal women. The inflammation brought on by excess weight may contribute to breast cancer development and progression.